2016
DOI: 10.1021/acsnano.6b06259
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Mo Nanocatalysts on N-Doped Graphite Nanotubes for Highly Efficient Electrochemical Hydrogen Evolution in Acid

Abstract: Developing noble-metal-free catalysts for electrochemical hydrogen evolution reactions (HER) with superior stability in acid is of critical importance for large-scale, low-cost hydrogen production from water electrolysis. Herein, we report a highly efficient and stable noble-metal-free HER catalyst, which is composed of Ni and MoC nanocrystals supported on N-doped graphite nanotubes. This catalyst shows very low overpotential (65 mV in 0.5 M HSO at a current density of 10 mA cm with a Tafel plot of 67 mV/dec) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 55 publications
2
70
0
Order By: Relevance
“…It is shown that the performance of W‐MoO 2 /MoC@PC ( η 20 =209 mV) is superior to that of Mo 2 C/C‐lamellas ( η 20 =220 mV), Mo x C‐G hybrids ( η 4 =475 mV), Mo 2− x Fe x C ( η 5 =240 mV), commercial Mo 2 C particles ( η 20 =225 mV), Mo 2 C nanoparticles supported on XC‐72R carbon black ( η 8 =200 mV), Mo 2 C nanowires ( η 20 =220 mV) and Mo 2 C nanosheets ( η 20 =260 mV) synthesized via pyrolysis of their MoO x /pphenylenediamine hybrid precursors, MoWON/NGR ( η 20 =270 mV) and so on. The performance of W‐MoO 2 /MoC@PC is inferior to that of Co 6 Mo 6 C‐G ( η 20 =183 mV), Mo‐W 18 O 49 ( η 20 =75 mV), MoO 2 @PC‐RGO ( η 20 =90 mV), NiMo‐NGTs ( η 20 =79 mV), and so on. The comparison reveals that W‐MoO 2 /MoC@PC exhibits comparable HER catalytic activity in comparison with most other Mo‐based nanostructures.…”
Section: Resultsmentioning
confidence: 98%
“…It is shown that the performance of W‐MoO 2 /MoC@PC ( η 20 =209 mV) is superior to that of Mo 2 C/C‐lamellas ( η 20 =220 mV), Mo x C‐G hybrids ( η 4 =475 mV), Mo 2− x Fe x C ( η 5 =240 mV), commercial Mo 2 C particles ( η 20 =225 mV), Mo 2 C nanoparticles supported on XC‐72R carbon black ( η 8 =200 mV), Mo 2 C nanowires ( η 20 =220 mV) and Mo 2 C nanosheets ( η 20 =260 mV) synthesized via pyrolysis of their MoO x /pphenylenediamine hybrid precursors, MoWON/NGR ( η 20 =270 mV) and so on. The performance of W‐MoO 2 /MoC@PC is inferior to that of Co 6 Mo 6 C‐G ( η 20 =183 mV), Mo‐W 18 O 49 ( η 20 =75 mV), MoO 2 @PC‐RGO ( η 20 =90 mV), NiMo‐NGTs ( η 20 =79 mV), and so on. The comparison reveals that W‐MoO 2 /MoC@PC exhibits comparable HER catalytic activity in comparison with most other Mo‐based nanostructures.…”
Section: Resultsmentioning
confidence: 98%
“…As expected, Co 0.7 Fe 0.3 CB showed the small Tafel slope of 36.2 mV dec −1 (Figure 2c), which is lower than CoCB (58.7 mV dec −1 ), FeCB (39.5 mV dec −1 ), IrO 2 /CB (87.3 mV dec −1 ), and CB (183.1 mV dec −1 ). Moreover, the electrical impedance spectroscopies (EIS) of Co 0.7 Fe 0.3 CB, CoCB, and FeCB electrodes were further measured to understand the electrode reaction kinetics . As depicted in Figures 2d and S3 (Supporting Information), the Nyquist plot of Co 0.7 Fe 0.3 CB possesses an obviously smaller semicircle than that of CoCB and FeCB, suggesting the much faster electron transport of Co 0.7 Fe 0.3 CB.…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peaks at 44.5°, 51.8° and 76.4° for Ni/C‐650 (without adding Mo source) in Figure b fit well with metallic Ni with fcc structure (PDF#04‐0850, labeled with •). Interestingly, the three particular peaks shifted by about 0.7° to the lower angle for MoC x /Ni‐650 in Figure b (labeled with ⧫) due to the Mo addition, which is believed to be the result of Ni−Mo alloying . In addition, the reflection at ca.…”
Section: Resultsmentioning
confidence: 96%
“…Encouragingly, Wang's group first synthesized molybdenum‐carbide‐modified N‐doped carbon vesicle encapsulating Ni nanoparticles (Mo x C−Ni@NCV) with outstanding catalytic HER performance . Li's group also reported a catalyst for HER, which was composed of Ni−Mo alloy and Mo 2 C nanoparticles supported on N‐doped graphite nanotubes (NiMo‐NGTs) . Very recently, Sun et al.…”
Section: Introductionmentioning
confidence: 99%